Effect of protein type, concentration and oil droplet size on the formation of repulsively jammed elastic nanoemulsion gels. Issue 47 (19th November 2019) - Patel, Aakash; Mohanan, Athira; Ghosh, Supratim
Abstract : Sodium caseinate (SC)-stabilized 40% oil-in-water nanoemulsions (NEs) could be transformed into elastic gels below a critical droplet size due to increase in ϕ eff by a thicker steric barrier of SC, while whey protein (WPI)-stabilized NEs remained liquid due to thinner steric barrier of WPI. Abstract : Rheology of sodium caseinate (SC) and whey protein isolate (WPI)-stabilized nanoemulsions (NEs) was investigated as a function of protein (1–5 wt%) and oil (30 and 40 wt%) concentration and storage time. For SC NEs, gel strength increased with an increase in protein and oil concentration and a decrease in droplet size and below a critical size transformed into a strong elastic gel that did not flow under gravity. Surprisingly, WPI NEs, although stable and had similar droplet size to SC NEs, did not form elastic gels. The stability of the NEs was studied for 3 months, and no significant change was observed. Considerable higher storage modulus ( G ′) of SC NEs compared to WPI NEs was attributed to an increased effective droplet volume fraction ( ϕ eff ) due to a thicker steric barrier of SC compared to WPI. The DLVO interdroplet potential was used to calculate the thickness of the charge cloud at an overall repulsive interaction of 1 k B T, which was added to the steric barrier to calculate the effective droplet size and ϕ eff . At the highest ϕ eff (0.79) for 5% SC NEs with 40% oil, the nanodroplets and associated repulsive barrier randomly jammed, leading to the formation of a strong elastic gel. For WPI NEs, maximum ϕ eff was 0.57, leading to a lack of jamming and viscous fluid-like behaviour. Re-plotting G ′ with ϕ eff for SC NEs with different protein concentration showed a linear trend followed by a rapid increase in G ′ at a critical ϕ eff, confirming the transition from weak glassy region to strong randomly jammed structure. SC-stabilized repulsively jammed NE-gels could be used as a novel soft material where a lower oil volume fraction and long-term stability is required.